Station Eleven [large type] : a novel - Mandel, Emily St. John, 1979- (Thorndike Press, 2014)
One snowy night Arthur Leander, a famous actor, has a heart attack onstage during a production of "King Lear." Jeevan Chaudhary, a paparazzo-turned-EMT, is in the audience and leaps to his aid. A child actress named Kirsten Raymonde watches in horror as Jeevan performs CPR, pumping Arthur's chest as the curtain drops, but Arthur is dead. That same night, as Jeevan walks home from the theater, a terrible flu begins to spread. Hospitals are flooded and Jeevan and his brother barricade themselves inside an apartment, watching out the window as cars clog the highways, gunshots ring out, and life disintegrates around them. Fifteen years later, Kirsten is an actress with the Traveling Symphony. Together, this small troupe moves between the settlements of an altered world, performing Shakespeare and music for scattered communities of survivors. Written on their caravan, and tattooed on Kirsten's arm is a line from Star Trek: "Because survival is insufficient." But when they arrive in St. Deborah by the Water, they encounter a violent prophet who digs graves for anyone who dares to leave.